THE INTERPRETATION AND ATTITUDE OF BODY SHAMING BEHAVIOR ON SOCIAL MEDIA (A DIGITAL ETHNOGRAPHY STUDY ON INSTAGRAM) - Kusnul Fitria; Yessi Febrianti (Pusat Penelitian dan Pengembangan Aplikasi Informatika, Informasi dan Komunikasi Publik (APTIKA dan IKP) Badan Penelitian dan Pengembangan SDM Kementerian Komunikasi dan Informatika, 2020)
The main objective of this research is to reveal the meaning and attitudes of victims of body shaming behavior on social media. Body shaming is the behavior of giving negative comments about a person's physical condition. Instagram is the social media most often used by body-shaming actors to carry out their actions. This research is a digital ethnographic study with primary data collection through digital observation, and in-depth interviews with five informants who were selected purposively. The results of this study, in general, encompass the description of three things which are: a) the awareness and experiences of the victim; b) the attitude of the victim; and c) the two ways interactions between the victim and the followers. The interpretation of the body shamming victims reflects body positivity and self-love form of content on their personal Instagram.